Fostering entrepreneurial creativity in secondary school students: Integrating foundational community knowledge into Design and Technology Education - Siew, Nyet Moi; Mad Noor Madjapuni; Jamilah Ahmad (Human Resource Management Academic Research Society, 2025)
Previous research introduced an Entrepreneurial Creativity (EC) module to help students market their product ideas but overlooked Foundational Community Knowledge (FCK) in generating community-tailored innovations. Studies suggest that FCK enables students to identify unique local problems, fostering innovation. However, empirical research on FCK’s role in EC within Design and Technology (D&T) education remains limited. This study assessed the validity, reliability, and feasibility of a newly developed FCK-based EC module using the ADDIE model. It also examined students’ ability to integrate FCK into the five EC stages—Investigation, Ideation, Design, Creation, and Commercialization—through an EC test. Students’ foundational community knowledge about timadang and bambangan fruit was examined. A descriptive research design was used, evaluating content validity via expert assessors and reliability and feasibility through Likert-scale responses from 30 Form Three students. The findings confirm the module’s acceptability and its impact on fostering EC within D&T activities. This study provides a framework for integrating FCK into secondary education to enhance entrepreneurial creativity.